Design of Realistic Mathematics Education Digital (RMED) in Era Society 5.0 - Safitri, Meilani; Aziz, M. Ridwan (Jurnal Pendidikan Matematika (JPM), 2023)
The era of society 5.0 is an era where technology becomes part of humans, in this era education is transformed into digital. This research is a descriptive qualitative research. The purpose of this study is to describe how the RMED design is in the era of society 5.0. data collection was done through literature study, in-depth interviews with teachers and students. The data obtained were then analyzed with a qualitative approach. The results of the study indicate that there is a need for further research and development related to RMED in the era of society 5.0